Some morphological factors of resistance of the bronchial wall to the development of chronic obstructive lung disease in smoking individuals - E. A. Gereng; I. V. Suhodolo; R. I. Pleshko; E. B. Bukreeva; A. A. Bulanova; I. S. Kremis; T. S. Klyushina (Сибирский научный медицинский журнал, 2020)
According to current epidemiological studies, chronic obstructive pulmonary disease (COPD) develops in only 15-20 % of smokers. This suggests that exposure to tobacco smoke is just a trigger of the pathological process, and other pathophysiological factors play a key role in the development of COPD. The aim of the study was to perform morphological analysis of bronchial mucosa features in smokers with and without chronic obstructive pulmonary disease.Material and research methods. Morphological and electron-microscopic analysis of biopsy samples of the bronchial mucosa of smoking patients with (n = 40) and without (n = 30) chronic obstructive pulmonary disease was carried out. The study involved men (80.2 % of men) and women aged 42 to 67 years (62.3 ± 2.24 years) with smoking experience of more than 20 years and smoking intensity of 20-45 pack-years. In the main group was a verified diagnosis of COPD. All patients of the studied groups underwent morphological, morphometric counting of bulk densities of various types of epithelial cells and structures of their lamina propria of the bronchial mucosa, as well as the density of inflammatory infiltrate and various cell populations, immunohistochemical (typing of CD4- and CD8positive lymphocytes, expression of transforming growth factor β1 receptors) and electron microscopic analysis of bronchobioptates.Results and discussion. Smokers without chronic obstructive pulmonary disease develop exudative inflammation, which does not violate the structural architectonics of the epithelial layer, but causes activation of proteinsynthetic and energy processes in the epithelial cells of the bronchial wall. With prolonged exposure to tobacco smoke associated with the development of chronic obstructive pulmonary disease, chronic neutrophilic inflammation forms in the bronchial mucosa, leading to a violation of the functional morphology of the vessels and epithelial cells of the bronchial mucosa, followed by remodeling of the bronchial wall.